King Cobra (Ophiophagus hannah) Venom L-Amino Acid Oxidase Induces Apoptosis in PC-3 Cells and Suppresses PC-3 Solid Tumor Growth in a Tumor Xenograft Mouse Model - Lee, Mui Li (Ivyspring International Publisher, 2014)
King cobra (Ophiophagus hannah) venom L-amino acid oxidase (OH-LAAO), a heat stable enzyme, has been shown to exhibit very potent anti-proliferative activity against human breast and lung tumorigenic cells but not in their non-tumorigenic counterparts. We further examine its in vitro and in vivo anti-tumor activity in a human prostate adenocarcinoma (PC-3) model. OH-LAAO demonstrated potent cytotoxicity against PC-3 cells with IC(50) of 0.05 µg/mL after 72 h incubation in vitro. It induced apoptosis as evidenced with an increase in caspase-3/7 cleavages and an increase in annexin V-stained cells. To examine its in vivo anti-tumor activity, we treated PC-3 tumor xenograft implanted subcutaneously in immunodeficient NU/NU (nude) mice with 1 µg/g OH-LAAO given intraperitoneally (i.p.). After 8 weeks of treatment, OH-LAAO treated PC-3 tumors were markedly inhibited, when compared to the control group (P <0.05). TUNEL staining analysis on the tumor sections showed a significantly increase of apoptotic cells in the LAAO-treated animals. Histological examinations of the vital organs in these two groups showed no significant differences with normal tissues, indicating no obvious tissue damage. The treatment also did not cause any significant changes on the body weight of the mice during the duration of the study. These observations suggest that OH-LAAO cytotoxic effects may be specific to tumor xenografts and less to normal organs. Given its potent anti-tumor activities shown in vitro as well as in vivo, the king cobra venom LAAO can potentially be developed to treat prostate cancer and other solid tumors.